DIVERGENCE OF OPINION AND LONG‐RUN PERFORMANCE OF PRIVATE PLACEMENTS: EVIDENCE FROM THE AUCTION MARKET. (14th February 2019) - Han, Jianlei; Pan, Zheyao; Zhang, Guangli
Abstract: In this article, we propose and construct a direct measure of investors' divergence of opinion based on auction bids data from private placements in China. We find that firms with higher bids dispersion generate lower long‐run stock returns after the issuance of private placements. This effect is economically significant and robust when controlling for market discount, earnings management, alternative dispersion measures, and self‐selection bias. Moreover, this negative relation is stronger for stocks with more stringent short‐sale constraints. Our findings therefore provide strong evidence for the overvaluation hypothesis.